(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
In surveys on insect pests of ornamental plants in Sicily and Liguria the Authors recorded the Diptera Agromyzidae Phytoliriomyza jacarandae Steyskal & Spencer, 1978. This species, of South American origin, is now present in Argentina, United States of America, Australia, New Zealand and South Africa, where it lives as leafminer of Jacaranda mimosifolia D. Don. (Bignoniaceae ). Leafmines with larvae and pupae of this species, that are here recorded for the first time in Italian and European fauna, have been observed on J. mimosifolia.